Asia's Transformation From Economic Globalization to Regionalization. - Meoller, Joergen Oerstroem (ISEAS - Yusof Ishak Institute, 2020)
Moeller's book The Veil of Circumstance, published in 2016, discussed the impact of technology, dehumanization and values on politics and economics. In this book, he takes the analysis one step further.